La Grama St. Augustine para Patios de Florida - Laurie Trenholm; Joseph Bryan Unruh; Travis W. Shaddox; Carlos F. Balerdi; Henrique Mayer (EDIS, 2018)
La grama o césped St. Augustine está muy adaptada a las zonas calurosas y húmedas (subtropicales) del mundo. Se cree que es nativa de las regiones costeras del Golfo de México y del Mediterráneo. St. Augustine es la especie de grama más usada en Florida. This is the Spanish-language version of ENH5/LH010, St. Augustinegrass for Florida Lawns. St. Augustinegrass is the most commonly-used lawn grass in Florida. This 10-page document describes its cultivation and management for Florida lawns. Written by L. E. Trenholm, J. B. Unruh, T. W. Shaddox, C. Balerdi, and H. Mayer and published by the UF/IFAS Department of Environmental Horticulture, January 2018. http://edis.ifas.ufl.edu/ep552